PD-L1 Expression in TNBC: A Predictive Biomarker of Response to Neoadjuvant Chemotherapy?. (14th December 2017) - Cerbelli, Bruna; Pernazza, Angelina; Botticelli, Andrea; Fortunato, Lucio; Monti, Massimo; Sciattella, Paolo; Campagna, Domenico; Mazzuca, Federica; Mauri, Maria; Naso, Giuseppe; Marchetti, Paolo; d'Amati, Giulia; et al.
Abstract : Triple negative breast cancer (TNBC) has an aggressive clinical behaviour, with a poorer prognosis compared to other subtypes. Recently, tumor-infiltrating lymphocytes (TILs) have been proposed as a predictive biomarker for a better clinical outcome and pathological response (pR) after neoadjuvant chemotherapy (NACT) in TNBC. These data confirm the role of the immune system in the neoplastic progression and in the response to therapy. We performed a retrospective analysis of 54 pre-NACT biopsies of TNBC and compared both the percentage of stromal TILs and the degree of PD-L1 expression with the extent of pR to standard NACT. A pathological complete response (pCR) was achieved in 35% of cases. Univariate analysis showed (i) a significant association between PD-L1 expression in ≥25% of neoplastic cells and the achievement of a pCR (p = 0.024 ); (ii) a significantly higher frequency of pCR in cases showing ≥50% stromal TILs (p < 0.001 ). However in the multivariate analysis only PD-L1 expression on tumor cells remained significantly associated with pCR (OR = 1, 13; 95% CI 1, 01–1, 27), suggesting that the expression of this biomarker could be associated with a subpopulation of TNBC more likely to respond to chemotherapy. These data need to be confirmed by larger studies.